A restatement of the natural science evidence base on the effects of endocrine disrupting chemicals on wildlife. Issue 1897 (27th February 2019) - Godfray, H. Charles J.; Stephens, Andrea E. A.; Jepson, Paul D.; Jobling, Susan; Johnson, Andrew C.; Matthiessen, Peter; Sumpter, John P.; Tyler, Charles R.; McLean, Angela R.
Abstract : Endocrine disrupting chemicals (EDCs) are substances that alter the function of the endocrine system and consequently cause adverse effects to humans or wildlife. The release of particular EDCs into the environment has been shown to negatively affect certain wildlife populations and has led to restrictions on the use of some EDCs. Current chemical regulations aim to balance the industrial, agricultural and/or pharmaceutical benefits of using these substances with their demonstrated or potential harm to human health or the environment. A summary is provided of the natural science evidence base informing the regulation of chemicals released into the environment that may have endocrine disrupting effects on wildlife. This summary is in a format (a 'restatement') intended to be policy-neutral and accessible to informed, but not expert, policy-makers and stakeholders.